2002
DOI: 10.1080/01443610252971203
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic uterine perforation in late pregnancy

Abstract: Case reportA 27-year-old primigravida with no significant history attended for booking at 13 weeks. Her booking examination and investigations were entirely normal. An ultrasound confirmed a single normal 13-week-sized intrauterine pregnancy and routine detailed scan at 20 weeks reported no abnormalities.The patient presented at 38 weeks +3 days with blood pressure of 130/90 mmHg, but without proteinurea. Serum biochemistry was normal. The plan was to induce labour in a week's time while the blood pressure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…El factor independiente más importante es la cicatriz uterina previa (perforación, resección cornual, resección de septo uterino, miomectomía, cirugía fetal, operación cesárea) (11). Se asocia también a pacientes con gran paridad (12), placenta increta o percreta, instrumentalización uterina en abortos, parto vaginal instrumental, inducción del trabajo de parto (13), abuso de cocaína (14) y causas idiopá-ticas (15). Estos factores se asocian a rotura uterina en tercer trimestre del embarazo o peri-parto y, aunque algunos investigadores informan sobre la ruptura uterina en mujeres no embarazadas (16,17) estas no son más que anecdóticas.…”
Section: Discussionunclassified
“…El factor independiente más importante es la cicatriz uterina previa (perforación, resección cornual, resección de septo uterino, miomectomía, cirugía fetal, operación cesárea) (11). Se asocia también a pacientes con gran paridad (12), placenta increta o percreta, instrumentalización uterina en abortos, parto vaginal instrumental, inducción del trabajo de parto (13), abuso de cocaína (14) y causas idiopá-ticas (15). Estos factores se asocian a rotura uterina en tercer trimestre del embarazo o peri-parto y, aunque algunos investigadores informan sobre la ruptura uterina en mujeres no embarazadas (16,17) estas no son más que anecdóticas.…”
Section: Discussionunclassified
“…The past injuries such as Cesarean delivery, hysteroscopic resection of uterine septum, myomectomy, and cornual resection are considered to be the causes of uterine rupture (5). It is reported that spontaneous rupture of unscarred uterus occurs in 1 in 15,000 (6). It may occur in a patient who has high parity (7), placenta increta or percreta, adenomyosis, abortion with instrumentation, manipulation during delivery, induced delivery by misoprostol (8), vigorous fundal pressure during delivery, cocaine abuse (9) and idiopathic cause (6).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that spontaneous rupture of unscarred uterus occurs in 1 in 15,000 (6). It may occur in a patient who has high parity (7), placenta increta or percreta, adenomyosis, abortion with instrumentation, manipulation during delivery, induced delivery by misoprostol (8), vigorous fundal pressure during delivery, cocaine abuse (9) and idiopathic cause (6). Most of the above listed causes shows that uterine rupture is mainly occur before or during labor after the second trimester.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, no cause can be identified, and these are considered idiopathic. [7][8][9] Magnetic resonance imaging and Doppler sonography can be used for the prenatal diagnosis of placenta increta. 10 However, the diagnostic value of sonography in prenatal diagnosis of an asymptomatic placenta increta is uncertain.…”
Section: Discussionmentioning
confidence: 99%